2003
DOI: 10.1073/pnas.0437998100
|View full text |Cite
|
Sign up to set email alerts
|

Infertility and aneuploidy in mice lacking a type IA DNA topoisomerase IIIβ

Abstract: We report that disruption of the mouse TOP3␤ gene encoding DNA topoisomerase III␤, one of the two mammalian type IA DNA topoisomerases, leads to a progressive reduction in fecundity. The litter size in crosses of top3␤ ؊/؊ mice decreases over time and through successive generations, and this decrease seems to reflect embryonic death rather than impaired fertilization. These observations are suggestive of a gradual accumulation of chromosomal defects in germ cells lacking DNA topoisomerase III␤, and this interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 44 publications
(53 reference statements)
2
55
0
Order By: Relevance
“…After several PBS washes, appropriate secondary antibodies were incubated for 1 hour at 37°C and slides were washed with PBS, and then mounted with Vectashield (Vector Laboratories). RAD51/DMC1 immunolabeling was performed as described in Kwan et al (Kwan et al, 2003). For in vivo experiment at least 30 cells were analyzed per animal.…”
Section: Immunofluorescencementioning
confidence: 99%
“…After several PBS washes, appropriate secondary antibodies were incubated for 1 hour at 37°C and slides were washed with PBS, and then mounted with Vectashield (Vector Laboratories). RAD51/DMC1 immunolabeling was performed as described in Kwan et al (Kwan et al, 2003). For in vivo experiment at least 30 cells were analyzed per animal.…”
Section: Immunofluorescencementioning
confidence: 99%
“…Whereas lower eukaryotes generally contain only one type IA topoisomerase, human cells, like most vertebrates, possess at least two Top3 homologues, hTOPIII␣ and hTOPIII␤ (Hanai et al, 1996;Ng et al, 1999). In mice, mutation of TOP3␣ causes embryonic lethality (Li and Wang, 1998), whereas mutation of TOP3␤ causes a shortened life span (Kwan et al, 2003). Interestingly, in S. cerevisiae and S. pombe, deletion of SGS1 or rqh1 ϩ can largely suppress the phenotypes caused by deletion of TOP3 or top3 ϩ , respectively (Gangloff et al, 1994;Goodwin et al, 1999;Maftahi et al, 1999;Chakraverty et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The physiological importance of the mammalian DNA topoisomerases was further underscored by studies of the IIβ enzyme, again initiated by Wei, who found that, although embryos lacking this enzyme can develop to term, they die at birth (90). He observed that these newborns showed no sign of any muscular movements before they expired, which suggested to us that they probably suffered a muscular and/or neural defect.…”
Section: Harvard: From Yeast To Micementioning
confidence: 96%
“…I therefore contacted Steve Burden at New York University Medical School about a plausible collaboration, and our joint experiments soon established that the mutant mice indeed showed neuromuscular defects. Innervation of the diaphragm muscles by motor axons, for example, is defective, leading to a breathing impairment and death at birth (90).…”
Section: Harvard: From Yeast To Micementioning
confidence: 99%